Global economic productivity losses from vision impairment and blindness. (May 2021) - Marques, Ana Patricia; Ramke, Jacqueline; Cairns, John; Butt, Thomas; Zhang, Justine H.; Muirhead, Debbie; Jones, Iain; Tong, Brandon A.M.Ah; Swenor, Bonnielin K; Faal, Hannah; Bourne, Rupert R.A.; Frick, Kevin D.; et al.
Abstract: Background: In the absence of accessible, good quality eye health services and inclusive environments, vision loss can impact individuals, households and communities in many ways, including through increased poverty, reduced quality of life and reduced employment. We aimed to estimate the annual potential productivity losses associated with reduced employment due to blindness and moderate and severe vision impairment (MSVI) at a regional and global level. Methods: We constructed a model using the most recent economic, demographic (2018) and prevalence (2020) data. Calculations were limited to the working age population (15–64 years) and presented in 2018 US Dollars purchasing power parity (ppp). Two separate models, using Gross Domestic Product (GDP) and Gross National Income (GNI), were calculated to maximise comparability with previous estimates. Findings: We found that 160.7 million people with MSVI or blindness were within the working age and estimated that the overall relative reduction in employment by people with vision loss was 30.2%. Globally, using GDP we estimated that the annual cost of potential productivity losses of MSVI and blindness was 410.7 billion ppp (range 322.1 - 518.7 billion), or 0.3% of GDP. Using GNI, overall productivity losses were estimated at 408.5 billion ppp (range 320.4 - 515.9 billion), 0.5% lower than estimates using GDP. Interpretation: These findings support the view that blindness and MSVI are associated with a large economic impact worldwide. Reducing and preventing vision loss and developing and implementing strategies to help visually impaired people to find and keep employment may result in significant productivity gains Funding: MJB is supported by the Wellcome Trust (207472/Z/17/Z). JR's appointment at the University of Auckland is funded by the Buchanan Charitable Foundation, New Zealand. The Lancet Global Health Commission on Global Eye Health was supported by grants from The Queen Elizabeth Diamond Jubilee Trust, Moorfields Eye Charity (GR001061), NIHR Moorfields Biomedical Research Centre, The Wellcome Trust, Sightsavers, The Fred Hollows Foundation, The SEVA Foundation, The British Council for the Prevention of Blindness and Christian Blind Mission. The funders had no role in the design, conduct, data analysis of the study, or writing of the manuscript.